GANGGUAN GEJALA DISLEKSIA PADA ANAK USIA DINI - Oktamarina, Lidia; Rosalina, Evita; Utami, Lucia Septiana; Duati, Syah Fitri Kurnia; Dzakiyyah, Cyndi; Sari, Riska Puspa; Julita, Monika Sales (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research is entitled Disorders of Dyslactic Symptoms in Early Childhood. The purpose of this research is to find out the symptoms of dyslaxia in early childhood. The research method is the type of research used is qualitative research with a case study method. Case studies are a type of qualitative research that has a function to investigate processes, obtain information and obtain in-depth information. While the case studied is the development of cognitive abilities of dyslexic children. Data obtained from observations of children and conducting interviews with parents and educators Dyslexic patients will have difficulty in identifying spoken words and converting them into letters or sentences. The results showed that Dyslexia is classified as a neurological disorder in the part of the brain that processes language. Dyslexia can cause symptoms that vary, depending on age and severity. In toddlers, symptoms can be difficult to recognise, but once the child reaches school age, symptoms will begin to show, especially when the child learns to read. Detection and treatment from an early age is proven to be effective in improving the ability of patients to read. Learning media in the form of pictures to help make it easier to introduce letters, distinguish letters until finally dyslexic children are able to read and write fluently in order to stimulate the development of dyslexic children by supporting what the child is doing, provoking the child to tell what is being done, for example, making triangles, squares, taking time to refreshing the child, helping the child to observe what is seen, for example in games, teaching children to understand symbols and playing puzzles together.